Pengaruh Perputaran Kas dan Perputaran Persediaan Terhadap Profitabilitas - Sarjito Surya; Ruly Ruliana; Dedi Rossidi Soetama (Akuntabilitas, 2017)
A discussion about the influence of cash turnover and inventory turnover toward profitability still shows inconsistencies. Therefore, this study is conducted to know the relationship between the cash turnover and inventory turnover on profitability and also how big the relationship is. This study was conducted at automotive and allied products in periods of 2010 – 2013 with a total study population of 18 (eighteen) companies registered in the Indonesia Stock Exchange. The sampling technique used in this study is purposive sampling and acquired 8 (eight) samples of companies. The analysis technique used is multiple linear regressions, both partial (t test) and simultaneous test (F test). The dependent variable is profitability while the independent variable is cash turnover and inventory turnover. The results of this study show both simultaneous and partialtest on cash turnover and inventory turnover do not have a significant effect on profitability.